Low Heat Flow in the Anhydros Basin, Aegean Sea, Recorded by Deep Subsurface Temperatures - Michael Manga; Masako Tominaga; Jonas Preine; Thomas A. Ronge; Sarah Beethe; Christian Hübscher; Iona McIntosh; Paraskevi Nomikou; Steffen Kutterolf; Tim Druitt; Alexis Bernard; Carole Berthod; et al. (Geophysical Research Letters, 2025)
Abstract Subseafloor in situ temperatures in a drilled hole in the Anhydros Basin, Aegean Sea, measured during International Ocean Discovery Program (IODP) Expedition 398, yielded a low heat flow (<0.023 W/m2) despite active magmatism and rifting in the region. The coldest and highest temperatures were 13.9°C at 52.5 m below seafloor (mbsf) and 15.5°C for the deepest measurement at 360.4 mbsf, respectively. Comparison of a heat transfer model with measurements suggests that sea bottom temperatures during the last glacial period were up to 10°C cooler than Holocene temperatures. The magnitude of Holocene warming co‐varies with the geothermal heat flow: if the former goes up the latter goes up. Low heat flow may arise from lateral removal of heat through deeper formations by gravity driven advection of fluids. Tectonic separation of the northwestern Anhydros Basin from the Christiana‐Santorini‐Kolumbo volcanic field may lead to minimal magmatic influences on heat flow.